2022
DOI: 10.1093/lifemedi/lnac055
|View full text |Cite
|
Sign up to set email alerts
|

Functional hepatobiliary organoids recapitulate liver development and reveal essential drivers of hepatobiliary cell fate determination

Abstract: During liver development, hepatocytes and cholangiocytes are concurrently differentiated from common liver progenitor cells and are assembled into hepatobiliary architecture to perform proper hepatic function. However, the generation of functional hepatobiliary architecture from hepatocytes in vitro is still challenging, and the exact molecular drivers of hepatobiliary cell lineage determination is largely unknown. In this study, functional hepatobiliary organoids (HBOs) are generated from hepatocytes. These H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 55 publications
0
8
0
Order By: Relevance
“…Another approach is adding integrative cues to the co-culture system, and organoids can be controlled to provide a human-like microenvironment [71][72][73]. Engineering approaches to produce human-like organoid co-culture systems include adding mechanical cues, nutritional needs and metabolic cues, related tissues such as stromal and immune cells, and biosensing technology [71][72][73][74][75].…”
Section: Functional Vasculature and Bile Ducts In Individual Mapsmentioning
confidence: 99%
“…Another approach is adding integrative cues to the co-culture system, and organoids can be controlled to provide a human-like microenvironment [71][72][73]. Engineering approaches to produce human-like organoid co-culture systems include adding mechanical cues, nutritional needs and metabolic cues, related tissues such as stromal and immune cells, and biosensing technology [71][72][73][74][75].…”
Section: Functional Vasculature and Bile Ducts In Individual Mapsmentioning
confidence: 99%
“…Advances in culture techniques and biomaterials hold promise for overcoming these challenges and unlocking the full potential of organoid research. A major limitation is the maintenance of cellular functionality and viability over time due to culture conditions, such as media composition and growth factors; as the volume of organoids increases, so does the demand for nutrients and oxygen [ 130 , 137 ]. At the same time, the accumulation of toxic metabolites causes cell death and necrosis.…”
Section: Cholangiocyte Organoids As a New Strategy For The Regenerati...mentioning
confidence: 99%
“…A recent study employing random lineage tracing to quantify the clonal expansion of hepatocytes in a normal liver revealed that 84.1% of hepatocytes did not proliferate, and only a small number of hepatocytes generated new cells to maintain the mouse liver mass in 9.5-9.7 months [16]. However, once the liver is injured from partial hepatectomy or harmful stimuli such as APAP and DDC, the regenerative process is initiated by hepatocyte self-renewal or hepatocyte reprogramming [1,[27][28][29]. Due to the different stimulating factors of injury, hepatocytes choose different regeneration modes, taking the path to liver reconstruction or tumorgenesis (Fig.…”
Section: Conversion Of Hepatocyte Identities In Response To Liver Injurymentioning
confidence: 99%